산업용 전력계통의 주파수 안정도와 전압 안정도를 고려한 부하차단 설계 - 김봉희; Kim, Bong-Hee (전기학회 논문지 P권, 53(3), 2004)
This paper has presented, taking an example of a gas separation plant, dynamic analysis on frequency decline caused by the over-loading at the generator and the knee point causing voltage instability due to reactive power required by re-acceleration of large induction motors, resulting in phenomena of failure in the conventional frequency load shedding. In order to resolve the voltage instability problem, a design of load shedding system employing under-voltage relays has been proposed to the industrial power system containing large induction motors in addition to the conventional load shedding employing frequency relays. For the purpose of dynamic analysis, models of gas turbine and governor, synchronous generator, brushless exciter, and induction motor are introduced.